The Conjugated Ionospheric Anomalies Preceding the 2011 Tohoku-Oki Earthquake - He, Liming; Wu, Lixin; Heki, Kosuke; Guo, Cong (Frontiers in Earth Science, 2022)
We present the conjugated ionospheric total electron content (TEC) anomalies prior to the 2011 Mw9.0 Tohoku-oki earthquake, Japan, observed by the Global Navigation Satellite System (GNSS) stations in northern Australia. The onset time of the anomaly, determined by the Akaike’s information criterion, is 41.5 minutes before the earthquake in Australia, which is very close to the time observed in Japan. The positive TEC anomalies in Australia emerged on the same longitude as the land area of NE Japan. This supports the model that electric fields within the ionosphere redistributed the electrons immediately before large earthquakes. However, the observed anomaly is shifted equatorward by ~500 km reflecting the difference in physical mechanisms between the two hemispheres. We also found that the geomagnetic declination near the conjugate point simultaneously started to change ~40 minutes before the earthquake, but its physical implication is yet to be explored.